Congenital oval or round window malformations in children: Surgical findings and results in 17 cases. (17th January 2016) - Vincent, Robert; Wegner, Inge; Derks, Laura S. M.; Grolman, Wilko
Abstract : Objectives/Hypothesis: To prospectively evaluate surgical findings and hearing results in children undergoing surgery for congenital oval or round window malformations (class IV malformations). Study Design: A nonrandomized, nonblinded, case series of prospectively collected data. Methods: Fourteen consecutive pediatric patients who underwent 17 surgical procedures for congenital oval or round window malformations in a tertiary referral center were included. Postoperative pure‐tone audiometry was available in 15 cases. The surgical technique for repair of the ossicular chain was dictated by the surgical findings at the time of surgery. The majority of the cases underwent ossiculoplasty using a Teflon piston, bucket‐handle prosthesis, or total ossicular replacement prosthesis. Associated surgical techniques included malleus relocation and oval window drill‐out procedure. The main outcome measures were preoperative and postoperative hearing status using four‐frequency (0.5, 1, 2, and 4 kHz) audiometry. Air‐conduction thresholds, bone‐conduction thresholds, and air‐bone gap were measured. Postoperative audiometry was performed at 3, 6, 9, 12, 18, and 24 months after surgery and at a yearly interval thereafter. Results: Postoperative air‐bone gap closure to 10 dB or less was achieved in 47%. A postoperative air‐bone gap closure to within 20 dB or less was achieved in 60%. Postoperative sensorineural hearing loss did not occur in this series. Conclusions: Middle ear surgery for class IV abnormalities is feasible, but success percentages are much lower compared to other types of congenital ossicular malformations. Surgeons should be particularly careful in case of facial nerve abnormalities on computed tomography or during middle ear exploration. Level of Evidence: 4 Laryngoscope, 126:2552–2558, 2016